KOMUNIKASI PERSUASIF KOMUNITAS HIJABERS PEKANBARU DALAM MEREKRUT WANITA BERJILBAB DI KOTA PEKANBARU - Maike Desyafitri; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The appearacnce of Hijabers Community makes a new happening clothing trend among vailed women. The existance of Hijabers Community may change the people perspective of veil from not stylish to the fashionable and up to date clothing. Proved community members who joined in the Hijabers Community Pekanbaru continue to increase. The aim of this recears is to know the proccess of perssuasive communication Hijabers Community Pekanbaru, techniques used Hijabers Community Pekanbaru, and media used by the Hijabers Community Pekanbaru to recruit the veiled women in Pekanbaru.This research used qualitative method with descriptive approach. The data collected by doing observation to participants, interview, and documentation. There are 8 participants taken by purposive technique for this research. This research used the interactive data analysis from Miles and Hubermen by using examination of validity technique thorough the extension of membership and triangulation.The result of research shows persuasive communication of Hijabers Community Pekanbaru in recruiting veiled women is persuasive communication by sending mails thorough media to the veiled women, then continue with communication to the committee of community about agreement or rejection for joining the community. For persuasive communication, the Hijabers Community uses appearance technique, doing the comparison, asking and listening,the communication style and also build the credibility. Moreover, Hijabers Community Pekanbaru use social media and mass media for better and easier information sharing.Keywords: Persuasive Communication, Hijab, Community, Hijabers.